Greek documentary papyri from Ptolemaic Egypt - Láda, Csaba A. 1965- (<<de>> Gruyter, 2008)
"This volume presents 14 hitherto unpublished Greek papyrus documents from Hellenistic Egypt, held at the Papyrus Collection of the Austrian National Library (Papyrussammlung der Österreichischen Nationalbibliothek) in Vienna."--P. [vii].
Keywords: Ptolemaic dynasty <305-30 B.C>; Österreichische Nationalbibliothek -- Papyrussammlung; Geschichte 323 v. Chr.-30 v. Chr.; Geschichte; Greeks -- Egypt -- History -- To 1500 -- Sources; Manuscripts, Greek (Papyri) -- Egypt; Griechisch; Papyrus; Egypt -- Civilization -- 332 B.C.-638 A.D. -- Sources; Egypt -- History -- 332-30 B.C. -- Sources; Ägypten -- Altertum; Quelle; Manuscripts, Greek (Papyri) - Facsimiles